Newtons Dynamic Laws (London Journal of Research In Science: Natural and Formal, 2026)
“Newton’s Dynamic Laws” are concerned with the motion of bodies in orbits. Newton has published his Laws in 1684, [1], and expanded this work into later editions [2]. This work was written in Latin but it was translated in many versions in English, e.g. [3]. Because of his revolutionary ideas and his mastery of geometry, his work was not largely amenable to a great sector of scientists and physicists. Several attempts, e.g. [4]-[5] were made to simplify and clarify these laws. Modern derivations may be found in e.g. [6].
Keywords: centripetal force; dynamic laws; kepler; Newton; planet orbit